2011
DOI: 10.1021/ja209570y
|View full text |Cite
|
Sign up to set email alerts
|

GPx-Like Activity of Selenides and Selenoxides: Experimental Evidence for the Involvement of Hydroxy Perhydroxy Selenane as the Active Species

Abstract: The reaction mechanism of the GPx-like oxidation of PhSH with H(2)O(2) catalyzed by selenoxides proceeds via formation of the hydroxy perhydroxy selenane, which is a stronger oxidizing agent than selenoxide. A hydroxy perhydroxy selenane intermediate was observed by electrospray ionization mass spectrometry and (77)Se NMR spectroscopy in reactions of selenoxide 8 with H(2)O(2).The initial velocity of oxidation of PhSH by H(2)O(2) with selenoxide 8 is 4 orders of magnitude higher than that of 8 without peroxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(102 citation statements)
references
References 69 publications
6
96
0
Order By: Relevance
“…There was hardly any activity for Ph 2 Se whereas the corresponding heterocyclic derivatives 2a and 2b were active under similar conditions; the 2a being more active. The observed activity in 2 could be due to stabilization of the proposed thioselenurane, R 2 Se(OH)(SR 0 ), intermediate species [20,22,53] through heterocyclic N/H secondary interactions.…”
Section: Catalytic Properties Of Organoselenium Compounds As Gpx Mimicsmentioning
confidence: 99%
“…There was hardly any activity for Ph 2 Se whereas the corresponding heterocyclic derivatives 2a and 2b were active under similar conditions; the 2a being more active. The observed activity in 2 could be due to stabilization of the proposed thioselenurane, R 2 Se(OH)(SR 0 ), intermediate species [20,22,53] through heterocyclic N/H secondary interactions.…”
Section: Catalytic Properties Of Organoselenium Compounds As Gpx Mimicsmentioning
confidence: 99%
“…However, on using all of these catalysts a decline in the yield was observed (entries [6][7][8]. It is notable that in the absence of the catalyst in the reaction the product was not observed (entry 9).…”
Section: Resultsmentioning
confidence: 99%
“…Over the past few decades organochalcogen compounds have attracted considerable attention due to their importance as reagents and synthetic intermediates in organic synthesis [1][2][3][4][5][6]. Several types of these compounds play a crucial role in biology and biochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…1,10-Phenanthroline ligand was tested for acceleration of the reaction, but the results indicated no significant yields improvement (Table 1, entry 6 vs. 7). Base and solvent screening revealed that KOH was optimal and DMSO was the most suitable (Table 1, entries [13][14][15][16]. Interesting, when the solvent changed to toluene (Table 1, entry 16), not any product was obtained.…”
Section: Letter Syn Lettmentioning
confidence: 99%